Peringkat Arus Investasi Indonesia Dalam Kerangka Asean-China Free Trade Agreement (Perbandingan Dengan Singapura, Malaysia, Thailand, Dan Vietnam) Ditinjau Dari Prinsip Fair And Equitable Treatment - Putri, Resha Roshana; Chandrawulan, An-An, Prof.; Amalia, Prita (Jurnal Hukum & Pembangunan, 2018)
In the investment sector in ASEAN-China Free Trade Agreement, all host countries are obligated to give the protections and legal certainty for investors in fair and equitable treatment principle. The investment relation in ACFTA is not only talking about the relation between Indonesia and China, but also how Indonesia shall compete with another ASEAN member states. Authors use juridical normative research method with literature studies. This research shows that Indonesia has not completely implemented the fair and equitable treatment for Chinese investors. There are the needs for changes in giving the protections for investors, specially in law and administration sides. The aim of giving this principle is to increase the investment flows between Indonesia and China